2019
DOI: 10.1093/ajcn/nqz192
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin supplementation does not improve left ventricular ejection fraction in ambulatory heart failure patients: a randomized controlled trial

Abstract: Background Thiamin, a water-soluble B-complex vitamin, functions as a coenzyme in macronutrient oxidation and in the production of cellular ATP. Data suggest that thiamin depletion occurs in heart failure (HF). Therefore, thiamin supplementation in HF patients may improve cardiac function. Objective We sought to determine whether oral thiamin supplementation improves left ventricular ejection fraction (LVEF), exercise toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 16 publications
2
18
2
Order By: Relevance
“…Whereas the trial led by Seligmann et al in the nineties showed that the beneficial effect of thiamine on left ventricular ejection fraction was associated with better functional capacity (improved by at least one NYHA class) [ 153 ], it was confirmed in a more recent study by Schoenenberger et al in which no change in walking time was observed in patients with improved left ventricular ejection fraction after thiamine supplementation period [ 165 ]. This raises questions about the real usefulness of thiamine supplementation in HF therapy, especially as other trials failed to demonstrate any benefit of vitamin B1 (dose ranging from 100 mg to 300 mg per day) although thiamine circulating level increased [ 15 , 166 , 167 , 168 ]. These studies not only failed to show a beneficial effect on cardiac function (FE) [ 15 , 167 ] but also failed to show an improvement in the quality of life of HF patients [ 15 , 166 , 167 , 168 ].…”
Section: B Vitamins In Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the trial led by Seligmann et al in the nineties showed that the beneficial effect of thiamine on left ventricular ejection fraction was associated with better functional capacity (improved by at least one NYHA class) [ 153 ], it was confirmed in a more recent study by Schoenenberger et al in which no change in walking time was observed in patients with improved left ventricular ejection fraction after thiamine supplementation period [ 165 ]. This raises questions about the real usefulness of thiamine supplementation in HF therapy, especially as other trials failed to demonstrate any benefit of vitamin B1 (dose ranging from 100 mg to 300 mg per day) although thiamine circulating level increased [ 15 , 166 , 167 , 168 ]. These studies not only failed to show a beneficial effect on cardiac function (FE) [ 15 , 167 ] but also failed to show an improvement in the quality of life of HF patients [ 15 , 166 , 167 , 168 ].…”
Section: B Vitamins In Heart Failurementioning
confidence: 99%
“…This raises questions about the real usefulness of thiamine supplementation in HF therapy, especially as other trials failed to demonstrate any benefit of vitamin B1 (dose ranging from 100 mg to 300 mg per day) although thiamine circulating level increased [ 15 , 166 , 167 , 168 ]. These studies not only failed to show a beneficial effect on cardiac function (FE) [ 15 , 167 ] but also failed to show an improvement in the quality of life of HF patients [ 15 , 166 , 167 , 168 ]. So far, the evaluation of thiamine supplementation as a new tool in HF therapeutics has shown mixed results and conclusions from the aforementioned studies are not clear because of the small sample size, short duration of follow-up, lack of any dietary assessment of thiamine intake, as well as the lack of precisely defined inclusion criteria.…”
Section: B Vitamins In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Another trial of 50 stable HFrEF patients (mean age 61.4 years) showed no change to LVEF after 1 month of thiamine supplementation (300mg/day), but there was an improvement in patient-reported peripheral edema [7]. A recent trial of 69 stable HFrEF patients (mean age 56.7 years) found no changes in LVEF and NT-proBNP after 6 months of thiamine supplementation (200mg/day) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults aged ≥65 years are more susceptible to thiamine deficiency [4], and may be more likely to benefit from thiamine supplementation. The two negative trials of thiamine supplementation did not enrich their sample for older age [7,8]. In addition, older adults are often underrepresented in randomized trials of pharmacologic agents in HF as they may not tolerate the target doses of HF medications or may have comorbidities that lead to exclusion [9].…”
Section: Introductionmentioning
confidence: 99%